Influence of the cranial base flexion on Class I, II and III malocclusions: a systematic review - Almeida, Kélei Cristina Mathias De; Raveli, Taísa Boamorte; Vieira, Camila Ivini Viana; Santos-pinto, Ary Dos; Raveli, Dirceu Barnabé (Dental Press International, 2017)
ABSTRACTObjective:The aim of this study was to perform a systematic review on the morphological characteristics of the skull base (flexion, anterior length and posterior length) and the concomitant development of malocclusions, by comparing differences in dimorphism, ethnicity and age.Methods: The articles were selected by means of electronic search on BBO, MEDLINE and LILACS databases from 1966 to 2016. A qualitative evaluation of the methodologies used on the articles was also performed.Results: Although the literature on this topic is abundant, only 16 articles were selected for the present systematic review. The cranial base angle itself does not seem to play a significant role in the development of malocclusions. In fact, the cranial base angle is relatively stable at the ages of 5 to 15 years.Conclusions: A more obtuse angle at the skull base, in association or not with a greater anterior length of the cranial base, can contribute to the development of Class II division 1 malocclusions. On the other hand, a more acute angle at the skull base can contribute to a more anterior positioning of the mandible and to the development of Class III malocclusions.

RESUMOObjetivo:o objetivo desse estudo foi realizar uma revisão sistemática sobre as características morfológicas da base do crânio (flexão, comprimento anterior e comprimento posterior) e o desenvolvimento concomitante da má oclusão, comparando as diferenças do dimorfismo, etnia e idade.Métodos: os artigos foram selecionados por meio de busca eletrônica nas bases de dados BBO, MEDLINE e LILACS, de 1966 a 2016. Uma avaliação qualitativa da metodologia dos artigos também foi executada.Resultados: ainda que a literatura seja abundante nesse assunto, somente 16 artigos foram selecionados para a presente revisão sistemática. O ângulo da base do crânio, por si só, não parece desempenhar papel significativo no desenvolvimento das más oclusões. De fato, o ângulo da base do crânio é relativamente estável dos 5 aos 15 anos.Conclusões: um ângulo mais obtuso na base do crânio, associado ou não a um comprimento maior, pode contribuir para o desenvolvimento da má oclusão de Classe II, divisão 1. Por outro lado, um ângulo mais agudo na base do crânio pode contribuir para um posicionamento mais anterior da mandíbula e para o desenvolvimento da má oclusão de Classe III.
Keywords: Malocclusion; Cephalometry; Growth; Skull base; Má oclusão; Cefalometria; Crescimento; Base do crânio